PERTANGGUNGJAWABAN INFLUENCER DALAM PEMBUATAN KONTEN PENGIKLANAN MELALUI SOCIAL MEDIA YANG MENGANDUNG INFORMASI PALSU (CONTOH KASUS KARTIKA PUTRI DAN DR. RICHARD LEE). - Sergio Solaiman; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
We often encounter advertising practices through social media, this can be in the form of a practice we know as endorsement, but it is not uncommon that endorsements made by influencers contain false information. Of these cases, why are the influencers who assist the endorsement process rarely penalized while they participate in the process of advertising a product that harms consumers? The author examines the problem by using normative research methods. The research data shows that there are weak clauses in the UUPK that do not clearly define who is meant by advertising business actors, and what form of concrete responsibility is the advertising business actors. This weakness results in most endorsements containing false information leaving the influencers and endorsers free from sanctions and only focusing on the producers of the goods or services. As in the example of the case when endorser promoting beauty and cosmetic products to her followers on Instagram, but further investigation has proven that the product contains toxic and dangerous ingredients and requires a doctor's prescription to be able to use it. The results of this study indicate the need for an element of caution for endorsers and influencers against endorsement offers that do not have a license, both in their products and businesses, by doing so they will not be penalized. It is recommended that further regulation of advertising content on social media is needed so that there is differentiation of responsibilities of endorsers and influencers according to their actions and caution.